Design and fabrication of a waveguiding organic double heterostructure light-emitting device : a milestone in the development of an electrically pumped polymer laser - Belton, Colin (Trinity College (Dublin, Ireland). School of Physics, 2003)
The development of an electrically pumped polymer laser fabricated using simple solution processing would revolutionise the optial data storage and communications industry. In order to achieve this, a research strategy, aimed at producing a waveguiding double heterostructure device, is developed whereby the relevant physical properties of a large number of conjugated polymers are investigated.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin